Flood Risk Reduction: A Government and Community Collaboration Perspective in Urban Communities - Harifuddin, Harifuddin; Azuz, Faidah; Apriningsih, Apriningsih; Nur Hayati, Afita; Abdurakhmanovich Yuldashev, Azim; Kuraesin, Arlis Dewi (Journal of Techno-Social, 2024)
Flooding is the responsibility of the government so it is necessary to anticipate it together with the community through social participation. This paper aims to analyse the role of the government in anticipating floods and to analyse the forms of community social participation in anticipating floods. The research method used is mixed research, qualitative quantitative design (explanatory sequential). Data collection used participant observation techniques, in-depth interviews, questioners, and documentation studies. The data was analysed quantitatively then qualitative research was conducted and the results were verified and ended with a conclusion. The results of the research obtained (1) the role of the government, among others: (i) preparing an early warning system, (ii) preparing evacuation facilities and infrastructure, including evacuation routes, and (iii) forming structural and non-structural flood volunteer teams. (2) Forms of community social participation include: cleaning and increasing the depth of waterways such as sewers and canals, raising the concrete walls of waterways, raising the foundations of houses, and organising the residential environment. The conclusion of this research is that the government’s role in flood mitigation in Makassar municipality focuses on things that prevent flooding. Forms of community social participation as a form of flood mitigation such as cleaning waterways, raising the walls of sewers and canals and so on